2008
DOI: 10.1002/ptr.2449
|View full text |Cite
|
Sign up to set email alerts
|

Citrus fruit flavonoids influence on neutrophil apoptosis and oxidative metabolism

Abstract: Citrus flavonoids are dietary antioxidants that may protect against oxidative stress linked to inflammation and reduce the risk of macromolecule damage caused by free radicals. Three citrus flavonoids - naringin, naringenin and hesperidin - have been examined for their ability to activate caspase-3, a marker of apoptosis execution, in human polymorphonuclear neutrophils in vitro, stimulated and non-stimulated with phorbol 12-myristate 13-acetate. The flavonoid potency to reduce reactive oxygen species generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 32 publications
2
20
0
1
Order By: Relevance
“…These results suggest the antiperoxidative potential of naringin, which has been reported earlier [5].…”
Section: Discussionsupporting
confidence: 72%
“…These results suggest the antiperoxidative potential of naringin, which has been reported earlier [5].…”
Section: Discussionsupporting
confidence: 72%
“…A reduction in neutrophils apoptosis has already been linked to several inflammatory conditions, including rheumatoid arthritis and acute respiratory distress syndrome (Chilvers et al, 2000), and there is some evidence that pharmacological manipulation can reduce or increase the inflammatory cell apoptosis (Ward et al, 1999). Recently, it was also reported that some antioxidant may revert the inhibition of human PMN neutrophil apoptosis, via caspas-3, a principle apoptosis executor, induced by reactive oxygen species (Zielinska-Przyjemska & Ignatowicz, 2008). Previously, we have shown that caffeoyl conjugates exert a marked notable activity on some of the biological functions of PMN implicated in the initiation and maintenance of inflammation (Góngora et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The formation zymosan-stimulated human neutrophils in inflammation (Zielińska-Przyjemska and Ignatowicz, 2008). As shown in Table 1, neohesperidin, which is a derivative of hesperidin, with free radical scavenging activity is expected to protect against gastric mucosal injury through the antioxidative mechanism.…”
Section: >200 >200mentioning
confidence: 99%